The toxicity in vitro of titanium dioxide nanoparticles modified with noble metals on mammalian cells. Issue 2 (25th October 2018) - Rosłon, Magdalena; Jastrzębska, Agnieszka; Sitarz, Karolina; Książek, Iza; Koronkiewicz, Mirosława; Anuszewska, Elżbieta; Jaworska, Małgorzata; Dudkiewicz‐Wilczyńska, Jadwiga; Ziemkowska, Wanda; Basiak, Dariusz; Rozmys?owska‐Wojciechowska, Anita; Olszyna, Andrzej
Abstract: The aim of the presented work was to evaluate the effect of modification of titanium dioxide nanoparticles with noble metals and their oxides on selected mammalian cells. The in vitro cytotoxicity studies of titanium dioxide (TiO2 ) nanoparticles modified with Au, Ag, Pd, Ag2 O, and PdO with reference to the unmodified TiO2 nanoparticles were presented. The evaluation of cytotoxic activity of the tested nanocomposite particles was carried out using three cell lines: Caco‐2 colorectal epithelial adenocarcinoma cells, BJ normal human skin fibroblasts, and L929 mouse fibroblasts. The in vitro studies included determination of cell viability after 24 and 48 hours of exposure to the nanocomposite particles, using the MTT assay, as well as flow cytometry with Annexin V‐FITC staining. Our results indicate that irrespectively of the kind of cell line and assay used, nanoparticles of unmodified titanium dioxide as well as those with addition of gold and palladium have a slight impact on cell viability at the investigated concentration range (10‐200 μg/mL). Nanoparticles with addition of silver (Ag and Ag2 O), were found to have significantly higher toxic effect, the level of which varied depending on the cell line and assay used.